MORPHOLOGICAL CHANGES OF THE MUCOSA OF THE STOMACH AND DUODENUM IN RATS WHEN THE IMBALANCE OF NITRIC OXIDE - Галінський О. О.; Ошмянська Н. Ю.; Макарчук В. А.; Севереновська О. В.; Руденко А. І. (World of Medicine and Biology, 2014)
We have investigated the changes in the morphological structure and distribution of endothelial and inducible NO-synthase (eNOs and iNOs) in the mucous membrane of stomach and duodenal ulcers in rats, caused 6 and 12-day injection of sodium nitroprusside and N-nitro-L-arginine. Under long-term excess NO has been observed atrophy of the gastric glands secreting cells with the compensatory decrease in the level of eNOS and improvement it in the duodenum, which is accompanied by elimination of iNOs+ cells in the studied parts of the gastrointestinal tract. The long- NO deficiency leads to structural damage of the gastric glands and tissue eosinophilia with an increased levels of iNOS, eNOS has been located not only in mucosal, but also in the G-cells of the glands. The imbalance in the NO-ergic system leads to disruption of the adaptive-compensatory mechanisms and progressive changes in the NO-synthase activity, disruption of the functional state of the gastroduodenal zone and to the loss of integrity of the morphological structure.
Keywords: gastric mucosa; duodenum; nitric oxide